Iman Dan Perbuatan Dalam Teologi Paulus Dan Yakobus: Sebuah Eksegesis Surat Roma 3:28, Efesus 2:8-10 dan Yakobus 2:24 - Heri Lim (Sekolah Tinggi Teologi Injili Jakarta, 2021)
One of the most heated discussions in Christianity is the discussion about faith and works which are contradictory in the theology of James and Paul. This article has the position that Paul and James are not contradicting one another, even their perspective is important to complete the Christian perspective as a whole when discussing faith and works in the doctrine of salvation. Within the framework of this article, the author will briefly examine the context of these letters, then exegesis some of the passages that become theological debate, and have implications for the lives of believers.